2017
DOI: 10.1101/236307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale discovery of mouse transgenic integration sites reveals frequent structural variation and insertional mutagenesis

Abstract: 1Transgenesis has been a mainstay of mouse genetics for over 30 years, providing numerous models of 2 human disease and critical genetic tools in widespread use today. Generated through the random 3 integration of DNA fragments into the host genome, transgenesis can lead to insertional mutagenesis if a 4 coding gene or essential element is disrupted, and there is evidence that larger scale structural variation 5 can accompany the integration. The insertion sites of only a tiny fraction of the thousands of tran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 38 publications
2
68
0
Order By: Relevance
“…Founders were identified and mated to wild-type C57BL/6NTac females. Analysis of integration site indicates insertion occurred at Chr11:40456787-40495044 and resulted in a 38.4 Kb deletion 69 . Copy number analysis was also performed on tail clips of the mice using the following primers and probe combination (spanning exons 2 and 3 of hSNCA gene):…”
Section: Methodsmentioning
confidence: 99%
“…Founders were identified and mated to wild-type C57BL/6NTac females. Analysis of integration site indicates insertion occurred at Chr11:40456787-40495044 and resulted in a 38.4 Kb deletion 69 . Copy number analysis was also performed on tail clips of the mice using the following primers and probe combination (spanning exons 2 and 3 of hSNCA gene):…”
Section: Methodsmentioning
confidence: 99%
“…The DNA also usually concatemerizes so the animal has multiple copies of the transgene and thus overexpresses the protein of interest. A study of 40 well-cited transgenic strains, many of which are used in neurodegeneration research, showed that about half had mutations at the insertion site, although little phenotypic outcome appears to be associated with these insertional mutation events (51). Injected constructs are often cDNAs under the control of non-endogenous promotors that are not expressed with the same pattern as the endogenous gene and are only expressed as the splice isoform encoded by the cDNA.…”
Section: Mouse Modeling: What Is the Question?mentioning
confidence: 99%
“…Among these, there was a significant (exact binomial test, n = 154 transcripts, P = 0.00014) enrichment of downregulated transcripts (n = 101 (66%) transcripts with reduced expression in TG compared to n = 53 (34%) transcripts with elevated expression in TG). Of note, differences for five of these transcripts are likely to reflect known deletions of the transgene integration sites for the CaMKIIα-tTA (encompassing Wdr60, Esyt2, Ncapg2, and Ptprn2) and MAPT (encompassing Fgf14) transgenes 30 . Given the high homology between transcribed regions of the human and mouse tau gene, we also find highly elevated levels of Mapt (Wald statistic = 11.11, log2 fold change = 0.50, FDR = 7.08E-25) (Supplementary Figure 5a) confirming stable activation of the MAPT transgene in TG mice; of note, human-specific MAPT sequence domains were only detected in TG RNA-seq datasets (Supplementary Figure 5b-c).…”
Section: The Rtg4510 Model Of Tau Pathology Is Characterized By Widesmentioning
confidence: 99%